Molecular Dynamics Revealing a Detour-Forward Release Mechanism of Tacrine: Implication for the Specific Binding Characteristics in Butyrylcholinesterase - Zhang, Zhiyang; Fan, Fangfang; Luo, Wen; Zhao, Yuan; Wang, Chaojie (Frontiers in Chemistry, 2020)
Butyrylcholinesterase (BChE) is a nonspecific enzyme with clinical pharmacological and toxicological significance, which was a renewed interest as therapeutic target in Alzheimer’s disease (AD) nowadays. Here all-atom molecular dynamics simulations of butyrylcholinesterase with tacrine complex were designed to characterize inhibitor binding modes, strengths as well as the hydrogen-bond dependent release mechanism. Four possible release channels were identified and the most favorable channel was determined by random acceleration molecular dynamics/molecular dynamics (RAMD MD) simulations. The thermodynamic and dynamic properties as well as the corresponding Detour-forward delivery mechanism were determined according to the classical molecular dynamics (MD) simulations accompanied umbrella sampling. The free energy barrier for the most beneficial pathway is about 6.75 kcal/mol, which reveals the specific binding characteristics in the active site. The residues including Ile69, Ser79, Trp82, Gly116, Thr120, Tyr332 and His438 were identified to play major roles in the stabilization of tacrine in the pocket of BChE, where hydrogen bonding and π-π interactions are significant factors. Tyr332 and Asp70, act as gate keepers, play crucial roles in the substrate delivery. The present results provide a basic understanding for the ligand transport mechanism depended on the BChE enzymatic environment, which is useful for the design of BChE inhibitors in the future.